(untitled) (Agroindustria, Sociedad y Ambiente, 2013)
This research has as main objective to validate the study of repeatability and reproducibility of laboratory testing for quality control of agroindustrial company as part of a metrological control. The development of the research was divided into several stages: diagnosis stage where data collection techniques were applied as direct observation , surveys , and the collection and analysis of historical data using descriptive statistics, step evaluation of methods to study repeatability and reproducibility which was selected the most appropriate, stage of outlining the metrological control that allowed to standardize the study of repeatability and reproducibility as part of metrological control and the implementation stage of the study that allowed us to determine the reliability of the tests performed laboratory . Finally it was concluded that the quality control laboratory does not meet all the requirements of the Technical Standard ISO 17025-2005 , analysts from laboratory quality control do not have adequate knowledge in metrology field , while the manager does , the study of repeatability and reproducibility can be applied only to the analysis of fast method moisture specifically on PC1, PN5 and PL3 lines , the method of averages and ranges for studying R & R was selected, it was possible to standardize the metrological control and eventually the results of the tests performed in the laboratory are not reliable. This research provides vital information to establish metrological control involving studies of repeatability and reproducibility.